Mie Gacoan in the Eyes of Millennials: Navigating Viral Trends and Brand Authenticity - Herdiansyah, Haris; Satriya, Rizky Bayu; Sianturi, Lewi Ronauli; Mutia, Zavira Keisa; Putri, Khaleivah Subhan (Universitas Indraprasta PGRI, 2025)
This quantitative study aims to examine the influence of trend adaptation and brand identity on consumer loyalty toward Mie Gacoan in Cikarang. A total of 200 late adolescent and early adulthood aged 20–25 years were selected using purposive sampling. Data were collected through a Likert-based questionnaire comprising three scales: trend adaptation, brand identity, and consumer loyalty. Reliability was assessed using Cronbach's alpha, while validity was tested through Pearson correlation. Classical assumption tests included normality testing using Monte Carlo Sig. (2-tailed) with a significance level of 0.05. Multiple regression analysis was employed to test the hypotheses. The findings show that, partially, trend adaptation significantly and positively affects consumer loyalty, whereas brand identity does not have a significant effect. However, simultaneous analysis indicates that both variables significantly influence consumer loyalty, with an R² value of 0.75 (75%). Trend adaptation is identified as the primary driver of consumer loyalty, while brand identity plays a vital role in ensuring long-term brand sustainability. The study underscores the need for trend-based innovation while preserving brand identity as a foundation of competitive advantage.